2006
DOI: 10.1063/1.2363959
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs metal-oxide-semiconductor capacitors with HfO2 gate dielectric grown by atomic-layer deposition

Abstract: The influence of various process conditions on the structural integrity and electrical properties of Al∕HfO2∕p-In0.13Ga0.87As metal-oxide-semiconductor capacitors was investigated. Room temperature capacitance voltage measurements revealed postdielectric deposition anneal reduced hysteresis by more than 0.5V and sulfur passivation of InGaAs improved the capacitance frequency dispersion properties as well as reduced interface trap density. At V=VFB−1V, the leakage current densities ∼1.3×10−7, 0.4×10−6, and 1.3×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 9 publications
2
44
0
Order By: Relevance
“…The sulfur treatment is expected to prevent reoxidation in ambient during transfer to the vacuum ALD system consistent with experiments on InGaAs 30,31 and GaAs. 32 After each step, samples were rinsed in deionized water for 1 min and then dried in N 2 gas.…”
Section: B Cleaning Studysupporting
confidence: 74%
“…The sulfur treatment is expected to prevent reoxidation in ambient during transfer to the vacuum ALD system consistent with experiments on InGaAs 30,31 and GaAs. 32 After each step, samples were rinsed in deionized water for 1 min and then dried in N 2 gas.…”
Section: B Cleaning Studysupporting
confidence: 74%
“…The untreated In 0.53 Ga 0.47 As sample has an IL oxide thickness of 1.9 nm and is comparable to the native oxide thickness of 2 nm found on In 0.53 Ga 0.47 As by Kobayashi et al 12 A number of recent publications have demonstrated that ALD deposition of Al 2 O 3 ͓using Al͑CH 3 ͒ 3 ͔ and HfO 2 ͕using Hf͓N͑CH 3 ͒ ϫ͑C 2 H 5 ͔͒ 4 ͖ on GaAs and In x Ga 1−x As substrates can reduce the thickness of interfacial Ga and As oxides during the ALD growth process. 6,7,12,13 This is referred to as an interfacial "self-cleaning process" and is most likely precursor dependent. The thickness of the IL oxide for the untreated sample ͑1.9 nm͒ indicates that limited or no interfacial self-cleaning process is occurring using the Hf͓N͑CH 3 ͒ 2 ͔ 4 and H 2 O water process.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the combination of a high electron mobility ($14 000 cm 2 /V s at low doping levels), suitable energy gap ($0.75 eV) and the fact that it can be grown lattice matched in InP, there has been a considerable focus of research attention on InGaAs with a 53% In concentration (i.e., In 0.53 Ga 0.47 As). The electrically active interface defects between the high-k gate oxide and the In 0.53 Ga 0.47 As surface, [7][8][9][10][11][12][13][14][15][16] and fixed charges within the high-k oxide, [15][16][17] have been studied in some detail in the literature. Charge trapping states can also be located in the transition region between the high-k oxide and In 0.53 Ga 0.47 As surface and are often referred to a "slow states" or "border traps".…”
Section: Introductionmentioning
confidence: 99%